2022
DOI: 10.21276/apjhs.2022.9.4s1.30
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Teneligliptin, and Teneligliptin Combined with Gabapentin on Alloxan-Induced Diabetic Neuropathy in Albino Mice

Abstract: Diabetic neuropathy is a nerve disorder manifested by different faceted condition affecting up to half of individuals with persistent diabetes. Symptoms associated with this disease such as nerve palsy, painful polyneuropathy, thoracoabdominal neuropathy, autonomic neuropathy, diabetic amyotrophy, mononeuropathy multiplex, caused by motor, sensory, and autonomic nerve dysfunction which affects peripheral nervous system, gastrointestinal, pain receptors, urogenital, and cardiovascular system. In this study, typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The dread of DM lies not in the probability of disease but in the complications induced. For the treatment of diabetic complications, combination medication is more effective than monotherapy (Kumar & Sharma, 2022;Sharma et al, 2012Sharma et al, , 2014Sharma & Srinivasan, 2009). In addition, it has been shown that Phytomedicine is an important means of treating diabetic complications (Hussain & Sharma, 2017a;Hussain & Sharma, 2017b;Sharma & Singh, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The dread of DM lies not in the probability of disease but in the complications induced. For the treatment of diabetic complications, combination medication is more effective than monotherapy (Kumar & Sharma, 2022;Sharma et al, 2012Sharma et al, , 2014Sharma & Srinivasan, 2009). In addition, it has been shown that Phytomedicine is an important means of treating diabetic complications (Hussain & Sharma, 2017a;Hussain & Sharma, 2017b;Sharma & Singh, 2019).…”
Section: Discussionmentioning
confidence: 99%